Improving strategic learning and self-regulation skills among underrepresented minority students in a summer research education training program - Edwards, Nishika T.; Khalil, Mohammed; Goodwin, Rich L.; Nathaniel, Thomas (Frontiers in Education, 2023)
This study examines the effect of educational interventions on strategic learning and self-regulation variables of underrepresented minority students (URMs) who participated in the NIH R25 Research education program. The LASSI instrument was administered to 21 URMs who participated in the intervention over two years. We collected pre-and post-intervention data before and after the educational intervention. There was a significant improvement (P<0.001) in all strategic learning and self-regulation parameters including attitude, concentration, information processing, motivation, selecting main ideas, self-testing, test strategies, and time management for the pre and postassessments. The results of this study indicate that self-regulated learning strategies in research education programs is important to help URM's chances of advancing along scientific and educational pathways.